Research Progress of Carrier-Free Antitumor Nanoparticles Based on Phytochemicals - Jiang, Siliang; Fu, Yu; Zhang, Xinyang; Yu, Tong; Lu, Bowen; Du, Juan (Frontiers in Bioengineering and Biotechnology, 2021)
Cancer is a major worldwide public health issue, responsible for millions of deaths every year. Cancer cases and deaths are expected to increase rapidly with population growth, age, and lifestyle behaviors that increase cancer risk. Long-term chemotherapy results in acquired drug resistance. Traditional treatment methods have limitations and cannot effectively treat distal metastatic cancers. Application of nanocarriers in multi-chemotherapy must be promoted. With research progress, the shortcomings of traditional nanocarriers have gradually become evident. Carrier-free nanodrugs with desirable bioactivity have attracted considerable attention. In this review, we provide an overview of recent reports on several carrier-free nanodrug delivery systems based on phytochemicals. This review focuses on the advantages of carrier-free nanodrugs, and provides new insights for establishment of ideal cancer treatment nanosystems.